A construção do profissionalismo na agronomia: trabalho, ciência e poder - MARQUES, Rogério dos Santos Bueno (2009)
The aim of this thesis is to comprehend the process of construction of the professionalism in Brazilian agronomy. We state that different strata of the working class face the labor world in different ways. Workers who are more educated and belong to middle classes, act and regard the labor process in a different way from blue-collars. We studied the process of formation of agronomists representative institutions to, in a second stage, discuss the concept of professionalism throw six non-structured interviews with experienced professionals. Labor market, client relations, State, knowledge are some of the concepts we discuss to build our thesis. We also research, in a more elementary level, the hierarchies inside the professional group in order to show how distinctions are made and what kinds of symbolic values are related to professional success among agronomists. A study of the professionalism ideology is also done so that we can discuss about some possibilities of understanding the labor as a human capability.